Applying the Technology Acceptance Model to Understand Student Adoption of Digital Technologies at Sunyani Technical University - Ofori, Ernest (Science and Technology: Developments and Applications Vol. 4, 2025)
In several developing nations, Information and Communications Technologies (ICT) are provided to instructors and learners without considering their attitudes and perceptions toward these technologies. Students’ attitudes have been identified as a predictor of the adoption of new technologies. The Technology Acceptance Model (TAM) has been extensively used to determine the extent of adoption and use of digital technologies in research. The model addresses the technical shortfalls of users by confronting some undesirable behavioural and perceptual traits that discourage the acceptance and usage of digital technologies. This study, therefore, sought students’ acceptance and use of digital technologies for the purpose of enhancing their learning. Inquiring from students how they use their digital devices and further rating their level of digital competencies (skills and knowledge) spurred the researcher to adopt an instructional delivery system through the application of the TAM to enable students to adopt, accept and incorporate these technologies into their learning in order to make learning flexible and self-paced. The quantitative method was used to answer the research questions that guided this study. This study aimed to apply the TAM to provide a descriptive analysis of how students adopt and use digital technologies in their remote locations. A survey questionnaire with 13 perceived ease of use, 13 perceived usefulness and 26 attitudes toward use items was designed in Google Forms and analysed using International Business Machines (IBM) Statistical Package for Social Sciences (SPSS) Version 23. The study also sought to use the model to address students’ perceptions and attitudes toward the use of digital technologies. The results of the Technology Acceptance Model indicated that students have developed the appropriate attitudes and perceptions to adopt and use digital technologies due to the fact that overall, students find digital technologies easy to use and very useful during learning. The study revealed that respondents developed positive attitudes and right perceptions toward the use of digital technologies during lessons because they gained more understanding and insight through the lively course content they offered. Respondents now have the belief that the intervention has helped them to develop the zeal to adopt and use digital technologies to enhance their learning.